QUANTITATIVE RESEARCH ON ROMANIAN CONSUMER PREFERENCES OF CERTIFIED ORGANIC FOOD - MANEA, Natalia; CETINĂ, Iuliana (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 18 (2016): Annales Universitatis Apulensis Series Oeconomica, 2016)
This paper aims to analyze consumer behavior Romanian certified organic products. The importance of this study is because in Romania, consumption of certified organic food is only 2% of total volume of the foods eaten. For it was used primary information through direct research, performed on a number of 130 respondents from Bucharest. The instrument used was a questionnaire which contained a number of 21 questions, opened, closed, dichotomous and multihotomice. Were considered the following variables: the category of persons who purchase organic products, products price, purchase frequency, respondents’ preferences on the place of purchase, perception on the quality of these products. It was found that price is one of the reasons why Romanians do not buy certified organic food.